2022
DOI: 10.1128/spectrum.00990-22
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of the Omicron (B.1.1.529) SARS-CoV-2 Variant Using a COVID-19 Diagnostic PCR Assay

Abstract: Rapid detection of the Omicron SARS-CoV-2 variant in patients’ respiratory tract samples may influence therapeutic choices, because this variant is known to escape from certain monoclonal antibodies. Our findings strengthen the importance of manufacturers’ efforts to improve the existing COVID-19 diagnostic PCR assays and/or to develop novel variant-specific PCR assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The study also reported that the mutant's infectivity was higher than that of the wild-type variant measured in Vero E6 and Calu-3 cells, and the mutations enhanced disease severity in the hamster model. Other studies later showed that R203K and G204R mutations can also be found in the B.1.1.529 and BA (Omicron) variants as well ( Hossain et al 2022 ; Ippoliti et al 2022 ; Jung et al 2022 ). While it is unclear if the mutations observed herein have similar effects to the R203K|G204R mutations, this finding warrants further investigation of the effects of mutations on nucleocapsid protein's linker domain on the virus.…”
Section: Resultsmentioning
confidence: 94%
“…The study also reported that the mutant's infectivity was higher than that of the wild-type variant measured in Vero E6 and Calu-3 cells, and the mutations enhanced disease severity in the hamster model. Other studies later showed that R203K and G204R mutations can also be found in the B.1.1.529 and BA (Omicron) variants as well ( Hossain et al 2022 ; Ippoliti et al 2022 ; Jung et al 2022 ). While it is unclear if the mutations observed herein have similar effects to the R203K|G204R mutations, this finding warrants further investigation of the effects of mutations on nucleocapsid protein's linker domain on the virus.…”
Section: Resultsmentioning
confidence: 94%
“…Many groups around the world have responded to the emergence of these highly infectious variants by developing several assays to detect viral variants of concern [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In this study, we collaborated with SBC public health officers and clinicians to rapidly develop and implement a simple and highly specific RT-qPCR assay to detect Omicron variants in residual diagnostic clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…As these samples were obtained in a period completely dominated by the Omicron variant (see below for identification details), the sample size in the second period was somewhat comparable with that of single non-Omicron variants (see below for identification details) in the first period. We had also studied part of these samples previously ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…We used the CleanPlex SARS-CoV-2 panel (Paragon Genomics, Hayward, CA) or the SARS-CoV-2 S gene kit (Arrows Diagnostics, Genoa, Italy) for samples ( n = 67 and n = 64, respectively) collected before 1 July 2021 and the COVIDSeq assay kit (Illumina, San Diego, CA) for samples ( n = 234) collected after 1 July 2021. This was the date of implementing the whole-genome sequencing (WGS)-based SARS-CoV-2 variant surveillance program in the Lazio Region in Italy ( 24 ), which is our study’s location. For the groups of 67 and 234 samples mentioned above, WGS data were also available (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%